Expiration of drugs in public hospital pharmacies of Sekhukhune District, Limpopo Province, South Africa - Mashishi, Kgabo Ambros (My University, 2015)
Background Drugs expiration in public hospital pharmacies is a concern to health professionals as the Department of Health spends a lot of money to buy drugs. The number of drugs which expire in public hospital pharmacies can give an indication of how the drugs are used, and consequently reflect on the disease prevalence for which the drugs are indicated for. Drugs cannot be used beyond expiry date. The purpose of this study was to determine the cause or causes, extent and costs of expired drugs in public hospital pharmacies of Sekhukhune District in Limpopo Province of South Africa. Methods Sekhukhune District has seven public hospital pharmacies. Data collection involved interviews conducted by the researcher from thirty-five participants with each hospital having five participants. All interviews were recorded by the use of a laptop voice recorder. Participants in each hospital involved a pharmacy manager, an additional pharmacist who had twelve months or more working experience within the facility under study, a clinical manager, a nurse who attends the hospital Drug and Therapeutics Committee and a medical practitioner who had twelve or more working experience within the facility under study. Results and conclusion In this study it was identified that, overstocking; prescribing tendencies by medical practitioners; delivery of short-dated drugs from the supplier; poor stock rotation and unreliably minimum and maximum order levels were cited as some of the reasons for stock expiration. The study found drugs expiration value to be above the set limit of 0.05% of the expenditure in a financial year. An expired stock value of R86 815 was found based on the data collected for 2010/2011 financial year.
Thesis (MPH.) -- University of Limpopo, 2015
Keywords: Drugs expiration; Hospital pharmacies; Drugs -- South Africa -- Limpopo.; Hospitals -- Drug distribution systems.; Drugs -- Prices.